Validitas Video Pembelajaran Berbasis Capcut Materi Sistem Peredaran Darah Manusia: Penelitian - Sefti Anjeli Darina; Siti Halidjah; Kartono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Many learning materials have not been delivered optimally due to time constraints and the many administrative demands that must be met by a teacher. This study aims to determine the level of validity of the development of CapCut-based learning videos on the human circulatory system. The type of research used is development research (Research and Development/R&D) with the 4D model (Define, Design, Develop, and Disseminate). Quantitative data were obtained from the results of product assessments by media validators and material validators, while qualitative data were obtained through suggestions and notes from media validators and material validators. The data collection technique was carried out using a questionnaire. The results of the study showed that the level of validity of CapCut-based learning videos was in the very valid category, with the following details: (1) media expert validation obtained a percentage of 87.5%, and (2) material expert validation obtained a percentage of 95%. Based on these results, it can be concluded that CapCut-based learning videos on the human circulatory system material meet the criteria of very valid and are worthy of being tested on students.